Effects Of Pretreatment And Enzymatic Hydrolysis On Oil Palm Frond For Use As Yeast Cultivation Medium - Eng, Kean Tiek (2012)
The advantage of acid hydrolysis is time consumed is much lower (10 minutes to 6 hours), as compared to enzymatic hydrolysis time is counted in days (Goldstein, 1983 and Wenzl, 1970). However, acid hydrolysis is hampered by non-selectivity and by-products formation from sugar decomposition (Fan et al., 1982). During acid hydrolysis, hemicelluloses are degraded to xylose, mannose, acetic acid, galactose and glucose; cellulose is hydrolyzed to glucose. At high temperature and pressure xylose is further degraded to furfural (Dunlop, 1948). Similarly, 5-hydroxymethyl furfural (HMF) is formed from hexose degradation, and HMF may be further degraded to form levulinic acid (Ulbricht et al., 1984).